Immune response and protection in gibel carp, Carassius gibelio, after vaccination with β-propiolactone inactivated cyprinid herpesvirus 2. (February 2016) - Zhang, Linlin; Ma, Jie; Fan, Yuding; Zhou, Yong; Xu, Jin; Liu, Wenzhi; Gu, Zemao; Zeng, Lingbing
Abstract: Herpesviral haematopoietic necrosis (HVHN) of gibel carp ( Carassius gibelio ) is a newly emerged infectious disease caused by cyprinid herpesvirus 2 (CyHV-2) and has caused huge economic losses in aquaculture operations. Currently, no effective methods are available for the control of the disease. In this study, β -propiolactone inactivated cyprinid herpesvirus 2 (CyHV-2) vaccine was prepared, and the immune response and protection in cultured gibel carp after vaccination was thoroughly investigated. This included blood cell counting and classification, phagocytic activity, lysozyme and superoxide dismutase activity, neutralizing antibody titration, immune gene expression analysis, and determination of the relative percent survival in vaccinated gibel carp. The results of blood cell counts indicated that the numbers of the red and white blood cells in the peripheral blood of immunized gibel carp increased significantly at day 4 and day 7 after vaccination ( p  < 0.01). The differential leukocyte count of neutrophils and monocytes were significantly different compared to the control group at day 4 and 7 and the percentage of lymphocytes reached a peak at day 21. The phagocytic percentage and phagocytic index peaked at day 4 post-vaccination. The lysozyme activity and superoxide dismutase activity were significantly increased compared to the control group ( p  < 0.01). The serum neutralizing antibody titer peaked (203.03 ± 13.44) at day 21. The qPCR analysis revealed that the expression of the immune genes interlukin 11 and complement component C3 were significantly up-regulated in the immunized group. The challenge test demonstrated that the immunized group had a relative survival rate of 71.4%. These results indicate that the inactivated CyHV-2 vaccine induced both non-specific and specific anti-viral immune responses that resulted in significant protection against HVHN disease and mortality in gibel carp. Highlights: The β -propiolactone inactivated CyHV-2 was firstly prepared for use as a killed vaccine. The immune response in gibel carp after vaccination was fully investigated. The inactivated CyHV-2 could produce a significant protection against the virus.